2016
DOI: 10.4103/0973-1482.179189
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of different treatment planning techniques with International Commission on Radiation Units and Measurements Report-83 recommendations in adjuvant pelvic radiotherapy of gynecological malignancies

Abstract: IMRT provided more protection than FIF plans at high dose volumes of the OAR; however, it did not show any superiority at low-dose volumes. The NTCP results supported IMRT for only small intestine protection. Because IMRT is increasingly used clinically, the comparison of NTCP will become more common in the near future. Therefore, new prospective studies with sufficient number of patients and appropriate NTCP models are needed for this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Like many studies, 4 , 24 , 25 , 26 , 27 , 28 our study discovered that IMRT for CCRT of cervical cancer did not worsen the survival outcomes compared to 3DCRT. Our study showed that the 2‐year, 3‐year, and 5‐year OS rates in IMRT and 3DCRT groups were 76.8%, 75.0%, and 58.3% and 81.3%, 73.7%, and 66.1%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Like many studies, 4 , 24 , 25 , 26 , 27 , 28 our study discovered that IMRT for CCRT of cervical cancer did not worsen the survival outcomes compared to 3DCRT. Our study showed that the 2‐year, 3‐year, and 5‐year OS rates in IMRT and 3DCRT groups were 76.8%, 75.0%, and 58.3% and 81.3%, 73.7%, and 66.1%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Third, none of the included studies described pelvic radiotherapy techniques or the dose limit of intestinal tissues. With the progress of radiotherapy techniques, different radiotherapy techniques employ different doses for intestinal tissues in pelvic radiotherapy[ 45 – 47 ]. However, the relationship between radiotherapy dose and changes in bacterial flora could not be clarified from these studies.…”
Section: Limitationsmentioning
confidence: 99%
“…With the four-field box technique, the bladder is exposed to the majority of the prescribed dose, and frequently a considerable part of the rectum is in the treatment field. By contrast, IMRT is a well-developed technique where critical organs just around the planning target volume (PTV) can be very well protected despite an irregular shaped PTV (11) . Field-infield (FIF) radiotherapy operates in the reverse way to inverse IMRT and is accepted as static IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…By applying an appropriate number of segments on 3D-CRT, a FIF plan can be obtained, and the negative effects of CRT in terms of conformity and homogeneity can be eliminated. Attempts have been made to determine which technique is superior with regard to target coverage, homogeneity, conformity and normal tissue dose (7,10,11) .…”
Section: Introductionmentioning
confidence: 99%